Adaptive management of the process of acquisition of intellectual property rights and commercialization of research in higher education institutions - Bruyeva, V. (Problems of Engineer-Pedagogical Education, 2020)
The article reveals the essence of the problem of managing the process of acquisition of rights and commercialization of intellectual property research in higher education institutions. The different vision of scientists on the protection of intellectual property created in higher education, the commercialization of intellectual resources as an alternative mechanism in the management of the process of acquiring intellectual property rights in higher education. Emphasis is placed on the obstacles of legal and economic aspects faced by universities and Ukrainian inventors in the creation and acquisition of rights to use the results of intellectual activity. The existing adaptive mechanisms that will improve the management of the process of acquisition of intellectual property rights and commercialization of research in higher education institutions have been identified and systematized. It is argued that the gradual and balanced introduction of adaptive mechanisms in the management of intellectual property rights in higher education institutions will increase the growth of inventive activity, commercialization and generally improve the innovation environment, infrastructure of higher education. Evidence is given that the development and implementation of adaptive mechanisms as components of adaptive management is a necessary condition for sustainable development of innovation capital in higher education. The mechanism of adaptive management of the process of acquisition of intellectual property rights in higher education institutions is offered. It is proved that the process of commercialization of intellectual property in higher education is the driving force in the transformation of rights into a profitable intellectual resource.